Educational videos in genetic counseling: Meeting patients where they are? - Julia Mahal; Carlotta J. Mayer; Sebastian Sailer; Melanie Wittenberg-Marangione; Johanna Tecklenburg; Elena S. Doll; Elias Staatz; Seraina P. Lerch; Hannah Wallaschek; Christian P. Schaaf; Beate Ditzen (Genetics in Medicine Open)
Purpose: This study examined the effects of self-developed educational videos on patient satisfaction and the physician-patient relationship in genetic outpatient clinics. Methods: Patients with suspected hereditary breast and ovarian cancer (HBOC, n = 311) or requiring exome sequencing for syndromic conditions (SYN, n = 52) were randomized to experimental or control groups. Before their consultations, the experimental group viewed videos detailing relevant genetic information. Patient and physician satisfaction and the quality of the physician-patient interaction were then assessed using questionnaires. Results: The videos were found to be understandable and useful. The video intervention did not affect patient or physician satisfaction scales or the physicians’ workload. However, there were significant interaction effects: The video intervention was associated with significantly lower satisfaction scores among patients with SYN. Additionally, in post-hoc tests, we partially found lower satisfaction with patient decision making, as well as increased physician workload in the SYN group compared with the HBOC group. Conclusion: Educational videos can improve patient satisfaction in HBOC consultations. In complex and less homogenous clinical situations, such as genetic consultation and testing for syndromic conditions, however, face-to-face physician-patient contact may be more appropriate to reduce stress and adequately address individual questions.